Clinical Features of Methicillin-Resistant Staphylococcus aureus (MRSA) Infection in Rabbits and its Zoonotic Potentials - Hamed, Dalia M.; Youssef, Ahmed I. (Pakistan Journal of Nutrition, 2013)
Staphylococcosis caused by methicillin-resistant Staphylococcus aureus (MRSA) infection in rabbitry is neglected as a cause of rabbit production impairment and zoonoses. This study aimed to monitor a rabbit flock problem associated with MRSA infection by following a rapid and simple sampling and diagnostic scheme. Resistance to antibiotics and zoonotic risk posed to human contact and food contamination were assessed. The identification of S. aureus was carried out by traditional bacteriological methods that confirmed with PCR. Results showed that a total of 80 (39.21%) out of 204 animals from apparently healthy rabbit were MRSA positive. The isolation rate was highest from nose/eye (26.47%), followed by skin affections (8.82%) and vaginal/perineum (3.92%) sampling sites. In post-mortem examination, MRSA was positive in 55 (26.96%) out of 204 animals. Isolation rate from lung was (22.05%) that was higher than from uterus (7.81%). Resistance to antibiotics was shown in 59.9% of the isolates. All tested isolates were methicillin and oxacillin resistant strains. Vancomycin and oxytetracycline also were resistant in 91.66% of strains. Ciprofloxacin is considered the drug of choice for treating multidrug resistant MRSA infections. MRSA was isolated from nasal swab of attendant and slaughterhouse workers (42.6%). In conclusion, high mortalities and infertility of rabbits caused by multi-drug resistant strains of MRSA with dissemination to environment and contamination of rabbit meat shed the light on its impacts on rabbit production and public health. Thus, large-scale epidemiological investigations of MRSA in rabbitry in Egypt are needed.